The Role Of Counselors In Enhancing The Psychosocial Adjustment Of Cadets During Flight Training Process - Islam, Fajar; Mintje, Quirina Ariantji Patrisia; Prasojo, Genny Luhung; Efendi (Sinergi International Journal of Psychology, 2023)
The flight training process at APIB is not an easy task. Cadets will be exposed to situations that test their physical, mental, and psychosocial limits. Good psychosocial adjustment enables cadets to cope with the pressure and stress that arise, maintain emotional balance, boost motivation, and build positive interpersonal relationships with instructors and fellow cadets. However, at API Banyuwangi, there is a lack of counselors available to provide psychological support and emotional guidance to the cadets. This research aims to investigate the importance of counselor presence in enhancing the psychosocial adjustment of cadets at API Banyuwangi during the flight training process. This research used a quantitative approach with data collection through questionnaires administered to pilot cadets at the Banyuwangi Flight Academy. The results of the study indicate that the presence of counselors at API Banyuwangi has a significant impact on the psychosocial adjustment of cadets. Counselors serve as empathetic listeners, providing emotional support, practical advice, and career guidance that help cadets overcome the psychological pressures and challenges of intensive flight training. A strong positive correlation between the role of counselors and the psychosocial adjustment of cadets is revealed through linear regression analysis, marked by high t-statistic values and very low levels of significance (p < 0.001).